The change in the use and exploit of common lands through three generations - Cabo, Paula (2016)
The common lands have a significant potential for sustainable rural development, which would be enhanced by new organizational and operational dynamics of the management bodies, determining factor for the diversification of economic and social activities, and consequent humanization of these lands (CMM, 2015; Rodrigues, 1999; Simões & Cristóvão, 2012; Bica, 2010). The present work describes a paradigmatic case of change in the use of common lands due to the transformation occurred in the local community, over 3 generations. Based on data obtained from field observation and personal interviews, it analyses the evolution of land use (including water resources) in the commons of a small village located 7 km from the town of Vila Real, Portugal on the right bank of Corgo river and east side of Alvão mountain, since the 2nd half of the twentieth century to the present day. These common lands extend for 30 ha located on the upper slopes adjacent to the Couto village, and are collectively owned by two local communities, the Couto village and Rebordinho hamlet. Both villages collectively own along with the neighbor village of Testeira, an upper plot of common lands located along the east ridge of the mountain. The common lands administration is carried out by the commoners in the person of President of the Governing Council, in accordance with the decisions taken at Commoners General Assembly. The commoners, inhabitants of local communities, according to local traditions and customs, are entitled to the use and fruition of the common lands, namely for pasturing animals, collection of wood for firewood and bushes for animals’ beds (such as gorse) and other fruitions, in particular, the use of spring water for irrigating crops. The study period comprehends 3 phases, according to the different generations presented. The first one, corresponding to the grandparents' generation, starts in the 2nd half of the XX century. It’s a period of intensive exploit of the common lands by the local communities for agro-forestry-pastoral purposes. In this phase, commons’ management task was performed jointly by a committee elected by the commoners of all common lands of the communities of the parish. At this stage begins the private appropriation of plots of common lands for house building. This appropriation made under cover of management committee’ family connections was target of popular contestation, and later legitimized by extending it to other commoners. By this way, it was established the policy of providing to commoners (and former commoners) plots for the construction of housing, and its transmission legalized by usucaption. For more than three decades the Couto village grew toward the Rebordinho hamlet, through private appropriation and urbanization of the common lands. This process was in place even until the beginning of this century, having just been abandoned by the impossibility of urbanization of the lots resulting from the new Vila Real County Master Plan, with the last plots given away being considered green zone. On the other hand, the common lands use for agriculture, forestry and pastoral activities was gradually phased out, with the change of the basis of local community economy. If in the early phase local communities were mainly agricultural, over generations, the main source of income ceased to be primary sector. The proximity to the urban center dictated the progressive change of labor standards, and although still living in the village, new generations are now working in the metropolis’ county and agricultural activity is only performed at the weekend and other free time and as supplement to the household income. This change in the economic basis of communities led to the common lands degradation, by lack of maintenance care, situation aggravated by a huge fire occurred 10 years ago. The second phase, the parents’ generation, is marked by the April 25 Revolution and the Portugal joined the European Economic Community - EEC. With plenty of EEC funds several land improvements have been made in common lands, in particular, put of irrigation water pipes and the opening and pave of rural roads. At the same time, animal traction led to traction motor. At this stage the use of common lands for the purposes of pasturing animals and collection of brushwood to animals’ beds was lost, and the gathering of firewood decays due to the raise of commoners’ purchasing power, thus exchanging the wood as a primary fuel in favour of electricity and gas. It remains the use of spring water for irrigating crops, now more intensely, with the change in cultural practices in favor of irrigated land. Finally, the generation of the sons, the current generation, currently lives a conflict motivated by the uses and customs of common lands using inherited from parents and grandparents. On the one hand, the developable land is scarce and expensive and, at the same time, there are vacant plots endowed to individuals for home building purposes that have never been urbanized or were sold for speculative purposes. Also the growth of Rebordinho community triggered the desire to "emancipation" and consequent claim for its own common lands, by splitting the existing common lands. Furthermore, the traditions regarding the use of commons’ spring water for irrigation does not suit the current working hours of local communities, increasingly rising conflicts between commoners.